CHANGING LANDSCAPE PATTERNS AND ITS EFFECT ON RISING LAND SURFACE TEMPERATURE OF LAHORE-PAKISTAN (Pakistan Journal of Science, 2022)
The study intaimsto evaluate the impact of landscape (Land use land cover) changes on Land surface temperature (LST) by using GIS and Remote sensing (RS) techniques in Lahore during 2017–2021.Supervised Maximum Likelihood classification method was used to classify the land use and land cover classes. For retrieval of Land surface temperature, the Landsat 8 (Band 10) product level 2 was used. Barren land and built- up area were identified as the most leading LULC classes respectively in the study area at the cost of vegetation cover and water bodies. The barren land class increased from 55.9% to 63.81% ,while the Built-up class also increases from 13.5% to 18.46% during 2017-2021.Whereas , vegetation and water bodies both are exhibiting the decline. The decline in vegetation class was reported from 29.58% to 17.6% over the time 2017 to 2021.Overall, 0.3 % decrease is observed in water bodies. In 2017 the 3◦C decline is observed in land surface temperature (LST) value than 2021.Built-up and Vegetation classes can contribute a significant role in variation of LST in comparison to the water bodies. These results will be very helpful to understand the LULC changes and eventually it will assist the land management authorities, policy maker and town planners as well.
Keywords: vegetation; Build-up Landsat; Supervised classification